Determination of risk factors associated with severity level of motorcycle–passenger car crashes - Zainal Abidin, Ahmad Noor Syukri (2019)
This study involves hospital-based on-the-spot (OTS) investigation on motorcyclepassenger car crashes with the aims to determine the risk factors involved in these crashes in which had represented approximately 38% of overall fatal motorcycle crashes in Malaysia. Standby period was performed in three 8-hour shifts in weekly alternate basis to ensure randomness of the investigated cases and to provide 24-hour coverage in order to represent the entire crash population. 55 crashes fulfilling the pre-determined criteria were investigated during one year data collection period in Kajang area. The crashes were reconstructed, analysed and injury details were coded according to Abbreviated Injury Scale (AIS). Morning crashes were 4.7 times more likely to occur during weekdays while night crashes had 6.1 times higher likelihood of occurrence during weekends. Male riders and riders aged >25 years old were found to be dominant (89.1% and 63.6% respectively), mostly as single riders (87.3%). Passenger cars were more often at fault (61.8%) as compared to motorcycles. However, no significance difference in impact speeds was found for different types of crash partners (p>0.05). 54.5% of the crashes involved situations whereby both vehicles were travelling in same direction, with one turning and the three most dominant crash classifications involved crashes at intersections. Side impacts were the highest crash configurations (40%) and 3.75 times more likely to result in riders suffering MAIS>3 injuries. 58% of the side impact crashes involved small angular side impacts and 61% involving motorcycles impacting the passenger cars. MAIS>3 injuries had an increasing trend with the increase of motorcycle travelling speed. Motorcycle travelling speed <15 km/h had 12.5 times higher likelihood to result in riders MAIS<2 injuries while lower extremities were the most injured body region sustained by riders (31 %). In regards to passenger car components, front tires were identified as the most damaged component caused by impacts from the motorcycles (21.8%), followed by front fenders and front bumpers (20% each). Moreover, MAIS3 injuries were most dominant when passenger cars’ front fenders and front bumpers were damaged (45.5% and 41.7%, respectively). ii The developed injury severity model has found that motorcycle impact speed, maximum wheel deformation and crash participant at fault status were significant predictors in predicting riders suffering MAIS>3 injuries. Riders were found to have a 1.5 likelihood increase in sustaining MAIS>3 injuries for every increase in impact speed and 23 times higher likelihood when passenger car was at fault. Meanwhile the injury type model concludes that motorcycle wheelbase deformation and crash participant at fault status were significant to predict riders lower extremity injuries. Riders were 4.8 times having the risk of suffering such injuries when crash partner was at fault and 1.02 times more likely to suffer such injuries with every decrease in wheelbase deformation. In conclusion, the study has presented meaningful information on evaluating risk factors and understanding the characteristics of motorcycle–passenger car crashes using real world data. It has also established introductory data on motorcycle riders’ injuries severity for future improvement of motorcycle safety, specifically in crashes with passenger cars.